Prediction of Adolescents‟ Self-efficacy based on Parent Adolescent Relationship with respect to Demographic variables: A Decision Tree Approach - U. , Sajitha; J , Parameswari (International Journal of Psychosocial Rehabilitation, 2020)
During adolescence the quality of relationship adolescents had with their parents as children changes. Most of the behaviors of children are influenced by parents, but during the adolescence stage, their behaviors are more influenced by peer groups. But still, parents play a crucial role in adolescent relationships. The parent-adolescent relationship may have a significant influence on the overall well-being of adolescents. Adolescents’ self-efficacy refers to individuals belief about their ability to solve a problem, reach a goal, and complete a task in a successful manner. The present study aims to examine adolescents’ self-efficacy based on their relationship with their parents and also in relation to demographic variables such as gender, class of study, type of institution, order of birth, family type, mother’s age, father’s age, and residing with or without parents. The researcher selected 756 adolescents of the age group 13-18 years from 14 schools in Thrissur city, Kerala, through a lottery method. The parent-child relationship scale (adolescent form) developed by Sajitha & Parameswari and the general self-efficacy scale by Schwarzer and Jerusalem were used to collect the data. The investigator employed percentage analysis and decision tree using SPSS. Results showed that different mother-father combinations based on their parent-child relationship and adolescents class of study and type of institution have played a prominent role in predicting self-efficacy.